Treaty for a Lost City : the Sino-British Joint Declaration - Lim, C. L. (Chin L.) (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
The Sino-British Joint Declaration was signed in 1984 and transferred control of Hong Kong to the People's Republic of China from the 1st July 1997. This sets the scene for the establishment of the Special Administrative Region (SAR) in Hong Kong, which has been at the heart of the civil unrest in 2019-2020, culminating in the National Security Law on 30 June 2020. In the 25th anniversary year of the handover of Hong Kong, C. L. Lim uses British archival sources to re-examine the Joint Declaration, the negotiations that led up to it, and its resounding significance that continues to the present day. Beginning with Margaret Thatcher's preparations for her Beijing trip, the book takes a chronological approach and offers a valuable, single-volume history of the Joint Declaration. In light of tumultuous current events in Hong Kong, Lim provides a vital, clear explanation of the legal complexities that have underpinned the relationships between China, Hong Kong and Britain since 1979.
Negotiations commence -- The Joint Declaration -- Twilight of colonial rule, democratic reform, the basic law and Bill of Rights : 1984-1997 -- The court and the canaries in a storm -- Foreign treaty relations -- Acts of State, Foreign Affairs, Defence -- Demos -- Patriotism, comprehensive jurisdiction, formal sllegiance : 2014-2017 -- Fundamental rights and the 2019 Extradition Bill -- The 2020 National Security Law -- Aftermath.
Title from publisher's bibliographic system (viewed on 01 Aug 2022).
Keywords: Hong Kong (China) -- International status; Sino-British Joint Declaration on the Question of Hong Kong -- (1984 December 19); Hong Kong (China) -- History -- Transfer of Sovereignty from Great Britain, 1997.; Constitutional history -- China -- Hong Kong; China -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- China